Heavy Metal Chemistry of Waste Water of Textile Dyeing Industries, Tongi, Gazipur, Bangladesh - Hossain, Saima; H.M. Selim Reza, A.; Saha, Sudip; Aminul Ahsan, Md. (International Journal of Advanced Chemistry, 2020)
The present research work shows the dominance of iron in the industrial waste water and river water samples of the investigated area of Gazipur district. The mean iron concentrations for both types of water samples are higher than the maximum permissible limits of WHO and NEQS. The excess amount of iron in water can cause health hazards of the human beings and ecosystem. Attempts should be taken to remove the excess amount of iron from the waters of the study area. On the basis of median concentration values of the heavy metals, they can be arranged as Fe>Zn>Ni>Cr>Pb. The factor analysis reveals the dominance of first two factors which comprise 83.298% of the total variance. The factor-1 is characterized by the contamination of Fe, Ni and Zn whereas factor-2 is dominated by the presence of Cu and Pb.Â